Ghrelin regulates hyperactivity-like behaviors via growth hormone signaling pathway in zebrafish (Danio rerio) - Guan, Kaiyu; Shan, Chunyan; Guo, Anqi; Gao, Xiang; Li, Xi (Frontiers in Endocrinology, 2023)
Ghrelin was originally identified as the endogenous ligand for the growth hormone secretagogue receptor and partially acts by stimulating growth hormone (GH) release. Our previous studies have identified GHRELIN is a new susceptibility gene for human ADHD, and ghrelin-depleted zebrafish (Danio rerio) display ADHD-like behaviors. Here, we performed RNA-sequencing analysis using adult ghrelinΔ/Δ zebrafish brain to investigate the underlying molecular change, and found that transcriptional expression of gh1 mRNA and it signaling pathway-related genes were significantly reduced, quantitative PCR reproduced these results in in ghrelinΔ/Δzebrafish larvae and the brain of adult ghrelinΔ/Δzebrafish. In addition, injection of recombinant human growth hormone (rhGH) can partially save the hyperactivity of ghrelinΔ/Δ zebrafish. Our results indicated that ghrelin regulate hyperactivity-like behaviors by mediating the GH signal pathway in zebrafish.